EARLY INFANT FEEDING AND THE RISK OF TYPE 1 DIABETES AGE : A SYSTEMATIC REVIEW - Al Ansoriani, Marogi; Rahayu Kosasih, Dina Mentayani; Alam Al Ansoriani, Nuansa Nur (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: In addition to genetic background, a number of environmental factors have been claimed to influence the development of type 1 diabetes (T1D), including infant diet. The aim: This study aims to show incidence, risk of early infanft feeding of DMT1 Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 146 articles, whereas the results of our search on SagePub brought up 74 articles. The results of the search conducted for the last year of 2013 yielded a total 49 articles for PubMed and 34 articles for SagePub. In the end, we compiled a total of 5 papers, 3 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Understanding the incidence, risk of early infanft feeding of DMT1